Introduction - Felder, Ekkehard; Jacob, Katharina; Schwinn, Horst; Busse, Beatrix; Große, Sybille; Gvozdanović, Jadranka; Lobin, Henning; Radtke, Edgar (Handbuch europäische Sprachkritik online, 2019)
This present volume, "Language institutions and language criticism", is directly linked to the first three volumes of our Handbook series and to the question, within a comparison of linguistic cultures, as to the ways in which the much-discussed and discursively constituted concept of linguistic standardisation of a national language has developed, along with the ways in which it is currently changing. This perspective reveals enlightening links to the first volume of the Handbook, "Critique of language norms", along with both the second and third volumes ("Standardisation and language criticism" and "Linguistic purism und language criticism").